Oral stomatitis and mTOR inhibitors: A review of current evidence in 20, 915 patients. (26th February 2018) - Lo Muzio, L; Arena, C; Troiano, G; Villa, A
Abstract : Background: Traditional treatment of malignancies with chemotherapeutic agents is often affected by the damage inflicted on non‐cancerous cells. Toxicities of the oral cavity, such as mucositis and stomatitis, are some of the most significant and unavoidable toxicities associated with anti‐cancer therapies. For such reason, in the last decades, newer targeted agents have been developed aiming to decrease the rates of side effects on healthy cells. Unfortunately, targeted anti‐cancer therapies also showed significant rate of toxicity on healthy tissues. mTOR inhibitors showed some adverse events, such as hyperglycemia, hyperlipidemia, hypophosphatemia, hematologic toxicities, and mucocutaneous eruption, but the most important are still stomatitis and skin rash, often reported as dose‐limiting side effects. Patients and Methods: A search of the literature was performed by authors on the PubMed online database using the following key words: "sirolimus" OR "everolimus" OR "temsirolimus" OR "deforolimus" OR "ridaforolimus" combined with the Boolean operator AND with the terms: "stomatitis" OR "mucositis" OR "oral pain." Titles and abstracts of 382 potentially relevant studies were screened; of these, 114 studies were excluded because they did not report the inclusion criteria. In the second round, 268 studies were read full‐text, but only 135 reported the inclusion criteria and were included for data extraction. Of the included studies, 95 referred to everolimus use, 16 to ridaforolimus, and 26 to temsirolimus (two studies referred to both everolimus and temsirolimus). Results: The incidence rate of stomatitis according to the agent used was 25.07% (3, 959/15, 787) for everolimus, 27.02% (724/2, 679) for temsirolimus, and 54.76% (598/1, 092) for ridaforolimus. All the three agents analyzed showed high rates of low‐grade stomatitis (G1–G2), while the onset of severe stomatitis (G3–G4) was rare. Conclusions: Analysis of the reports with patients treated with everolimus, temsirolimus, and ridaforolimus showed a clear prevalence of stomatitis grade 1 or 2. These data differ from that of patients treated with conventional chemotherapy in which mucositis is predominantly of grade 3 or 4.